Carbon and nitrogen stocks and distributions associated with different vegetation covers and soil profiles in Abisko, northern Sweden - Hugo M.G. Potier; Xavier Raynaud; Yannick Agnan; Alienor Allain; Maryse Castrec-Rouelle; Veronique Vaury; Luc Abbadie; Marie A. Alexis (Arctic Science)
The composition of vegetation cover in Arctic environments is evolving due to climate change. This study focused on estimating carbon and nitrogen stocks in vegetation and soil for different Arctic habitats (i.e., sub-ecosystem environments) with contrasted plant communities and soil profiles, to better understand the spatial variation of these stocks and the relationships between aboveground vegetation and soil characteristics in these environments. Vegetation composition and soil characteristics were measured in different habitats in a mire and a heathland ecosystem in northern Sweden. Multivariate analyses were used to define dominant vegetation and soil profile types, and carbon and nitrogen stocks were computed and compared across these types. Shrub-dominated and graminoid-dominated vegetation types presented similar carbon stocks but different nitrogen stocks, and shrub-dominated environments presented significantly higher proportions of their stocks distributed in the long-lived (i.e., woody) compartment. Soil stocks varied considerably between ecosystems. However, no clear relationships could be established between current vegetation community composition and soil carbon and nitrogen stocks across environments. The increase in shrub or graminoid abundance may affect carbon and nitrogen cycles most through biomass distribution between plant compartments rather than through the absolute stocks they represent. Ultimately, in Arctic and subarctic ecosystems experiencing climate change, the interactions between plant biomass composition and soil characteristics could have contrasted consequences for ecological functioning and C and N cycles.